2011
DOI: 10.1007/s00259-011-1906-x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of correction for tissue fraction effects in lung PET: preliminary findings

Abstract: The proposed tissue fraction correction method is a promising technique to account for variability of density in interpreting lung PET studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 24 publications
3
99
0
2
Order By: Relevance
“…CT mean was moderately correlated with PFT and SP-D and weakly correlated with KL-6 but was not significantly correlated with patient prognosis. SUV TF , which reflects 18 F-FDG accumulation in lung tissue without the influence of CT attenuation (17), showed significant correlations with %DLco, KL-6, and SP-D, but these correlations were weaker than those shown by SUV mean . Although univariate analysis showed that SUV TF was a prognostic factor, multivariate analysis showed that it was not an independent predictor.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…CT mean was moderately correlated with PFT and SP-D and weakly correlated with KL-6 but was not significantly correlated with patient prognosis. SUV TF , which reflects 18 F-FDG accumulation in lung tissue without the influence of CT attenuation (17), showed significant correlations with %DLco, KL-6, and SP-D, but these correlations were weaker than those shown by SUV mean . Although univariate analysis showed that SUV TF was a prognostic factor, multivariate analysis showed that it was not an independent predictor.…”
Section: Discussionmentioning
confidence: 80%
“…Hence, SUV mean represents the uptake by apparently normal or less-affected lung parenchyma in each patient. SUV TF has been introduced as a TF-corrected SUV in a recent article, to demonstrate more appropriate metabolic characteristics independent of degree of aeration (17). SUV TF was calculated using the parameter k, a coefficient representing the proportion of stromal component in the targeted VOI, applying the CT image acquired on the PET/CT scan.…”
Section: Image Analysismentioning
confidence: 99%
“…V B can be estimated from the compartment model. V A can be determined from the attenuationcorrection CT scan after downsampling to match the resolution of the PET image (37,38). Therefore, this model enables isolation of the signal from all nonair and nonblood lung components within the ROI (C T ðtÞ).…”
Section: Analysis Methods and Their Applications In Lung Diseases Quamentioning
confidence: 99%
“…The SUV is also affected by air within ROIs. Normalizing it for the air fraction will likely improve its accuracy as a reflection of lung cell metabolic activity (38). Normalization for blood (such as the tissue-toblood ratio, as explored in a dog model of ARDS (46)) may further improve the accuracy of V B ; however, whether this approach is comparable to correcting for V B as measured by kinetic analysis or other imaging (such as 15 O-CO scans) remains to be seen.…”
Section: Analysis Methods and Their Applications In Lung Diseases Quamentioning
confidence: 99%
See 1 more Smart Citation